The importance of education for the reallocation of labor: Evidence from Swedish linked employer-employee data 1986 - 2002 - Marie Gartell; Ann-Christin Jans; Helena Persson (Institute for Labour Market Policy Evaluation (IFAU), 2007)
Using employer-employee data covering the whole Swedish economy over a uniquely long time period from 1986 to 2002, we examine how job flows and worker flows have been distributed both on an aggregate level and across educational levels. We find that job and worker flows vary by educational level, not only with respect to magnitude and variation, but with respect to direction as well. Our results show that analyses that do not account for the educational level of workers can be very misleading.
Keywords: I20; J21; J23; 330; Linked employer-employee data; job and worker flows; education; Arbeitsplatzsuchmodell; Bildungsniveau; Statistische Bestandsanalyse; Schweden